Iron deficiency and anaemia in athletes - Peeling, P.; McKay, A.; Sim, M. (Nutritional Anemia, 2022)
Iron deficiency (ID) is a common condition in athlete populations, resulting from the myriad of exercise-related mechanisms that underpin iron utilisation and iron loss. This mineral is fundamental to exercise performance, physical capacity and human adaptation to training; however, these factors are compromised when ID is left to progress in severity to states of anaemia. Accordingly, nutritional interventions in the form of increased dietary iron intake, oral iron supplementation and/or parenteral iron administration may all be considered as part of any plan to treat ID. The appropriate treatment strategy should be reflective of the deficiency severity and should be planned in consultation with trained dietetics and medical providers. The following chapter considers this prospect in detail.